Mighty Giants - BENTON, Michael (Discovering Dinosaurs, 2015)
Why did dinosaurs have massive bodies and long necks? What made Tyrannosaurus rex so fearsome? Travel back to the dinosaur age to learn about how the biggest, heaviest and fiercest creatures on Earth lived.